Various forms of alcohol use and their predictors among pregnant women in post conflict northern Uganda: a cross sectional study - Apophia Agiresaasi; Goretti Nassanga; Gakenia Wamuyu Maina; Juliet Kiguli; Elizabeth Nabiwemba; Nazarius Mbona Tumwesigye (BMC, 2021)
Abstract Background Alcohol use during pregnancy has been associated with several births and developmental disorders. This study set out to determine the various forms of alcohol consumption among pregnant women and their predictors in post conflict Northern Uganda. Methods In the months of May to June 2019, we conducted a cross sectional study among 420 pregnant women seeking antenatal care services at both Government and private health facilities in Gulu, Kitgum and Pader districts in Northern Uganda. We asked them about consumption of various alcoholic beverages. A three stage stratified cluster sampling approach was used and study participants randomly selected from health facilities of interest. We used descriptive statistics to estimate the prevalence of various forms of alcohol use. The chi- square test and logistic regression were used to assess associations of alcohol use among respondents and their socio - demographic and other characteristics. Results Overall 99 women (23.6%) reported current alcohol use (any amount). Up to 11% (N = 11) of all drinkers were identified by the AUDIT to be women with problem drinking behavior, 8% (N = 8) of women reported hazardous drinking and only four (4%) were women with active alcohol dependent behavior. Predictors of maternal alcohol use included pre-pregnancy alcohol consumption, knowledge, attitude, education level, parity and residence. Conclusions This study indicates that alcohol use (any mount) during pregnancy is high while alcohol dependence, problematic and hazardous drinking is low. Knowledge and attitude were important predictors of alcohol use. While alleviating alcohol use, development partners and relevant government departments should consider communication and other interventions that increase knowledge and risk perception on maternal drinking. Other risk factors that predict maternal drinking such as prior alcohol use, residence and parity should be mitigated or eliminated.